Stories of Resilience: Libraries Supporting Young Voices - Chaymae Mekanni (21693180) (2025)
The Museum of Islamic Art Library organized a writing competition for the young people of Gaza who came to Qatar after the Israeli attack since 7 October 2023. This initiative resulted in the creation of a book titled Tales from Gaza, which includes all the stories submitted to the competition. More than just a contest, this initiative served as a means, an opportunity and an open space for expressing the feelings of children and young people who have endured hardships and suffering beyond what we can imagine. For some, it provided a chance to unleash their imagination in worlds far removed from the noise of reality, highlighting their writing talents and allowing them to explore stories woven from both reality and fantasy. This competition played a crucial role in the library’s vision to enhance cultural, artistic and creative communication among children and youth around the world. It opened the door for sharing creative experiences and strengthened their ability to integrate into society and express themselves freely. Other Information Presentation was given at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda